Efficacy assessment of commercial mosquito coils and associated pyrethroid resistance mechanisms in Aedes aegypti from Indonesia / Amelia Yap Zheng Hua - Amelia Yap , Zheng Hua (2018)
Aedes aegypti Linnaeus is the main vector of several arthropod-borne viral infectious diseases globally. Relentless vector control efforts have been performed to curtail disease transmissions, with insecticides remain as the first line of defence in Indonesia. With a dearth of published information, this is the first related report on the efficacy of mosquito coils in Indonesian Aedes aegypti. Aedes aegypti mosquitoes were sampled from nine regencies in Indonesia and tested against commercially available local pyrethroid-based mosquito coils containing d-allethrin, transfluthrin and metofluthrin to assess insecticide susceptibility profile. In accordance with the WHO resistance indicators, mosquito populations from Denpasar, Mataram, Kuningan, Padang, Samarinda and Sumba Timur were resistant (< 90% mortality rate) whereas populations from Manggarai Barat, Dompu and Pontinak were susceptible (≥ 98% mortality rate) to the active ingredients assayed. Additionally, the knockdown rates between d-allethrin and transfluthrin, d-allethrin and metofluthrin, as well as transfluthrin and metofluthrin displayed significant associations, portraying the presence of cross-resistance within the pyrethroid insecticides. The presence of resistance led to biochemical and molecular studies to characterize the mechanisms involved. In enzyme assays, esterases (ESTs), glutathione-S-transferases (GSTs) and mixed function oxidases (MFOs) were examined. Inconsistent trends in enzyme activities were demonstrated in Indonesian Ae. aegypti. MFOs were found to be associated with the pyrethroid resistance of Indonesian Ae. aegypti. No significant correlations were shown between pyrethroid resistance phenotype and α-ESTs, suggesting the marginally-exceeded enzyme levels relative to the reference strain in some pyrethroid susceptible populations were causative factor for insecticide resistance in other oups of insecticides. However, significant correlations were demonstrated between β- ESTs and pyrethroid resistance phenotype. The lowest enzyme levels in GSTs indicated this enzyme was not predominant in causing pyrethroid resistance, despite the presence of significant correlations. Metabolic-mediated resistance did not comprehensively explain the elevated resistance status to pyrethroids in mosquito coil bioassay because of the existence of another mechanism commonly detected in pyrethroid-resistant Ae. aegypti. Target-site alterations to pyrethroids in mosquitoes is caused by mutations in voltage-gated sodium channel (Vgsc), usually known as knockdown resistance (kdr). Three point mutations were screened, namely S989P, V1016G and F1534C mutations. Both S989P and V1016G mutations showed higher frequency of homozygous resistant (RR) than homozygous susceptible (SS) genotype whereas for F1534C mutation, most of them were homozygous susceptible (SS). The co-occurrence of the S989P and V1016G mutations were discovered. Additionally, significant correlations were demonstrated between the allele frequencies of the V1016G mutation and the survivability rates as well as resistance ratios in pyrethroid adult bioassays. This signifies the V1016G can contribute more to the insensitivity of Vgsc than the F1534C. In conclusion, this study reveals the first evidence of inefficacy of mosquito coils to some Ae. aegypti populations from Indonesia, urging for a revamping of the vector control system. Metabolic-mediated resistance and target-site alterations were also proven to cause pyrethroid resistance in Indonesian Ae. aegypti, providing insights into the evolution and adaptation of Indonesian Ae. aegypti.